A CRITICAL RACE THEORY ANALYSIS OF PUBLIC PARK FEATURES IN LATINO IMMIGRANT NEIGHBORHOODS. (29th September 2016) - García, Jennifer J.; Gee, Gilbert C.; Jones, Malia
Abstract: The present-day location of public parks should be understood in the proper social and historical context of residential segregation and urban development. In Los Angeles, discriminatory practices such as restrictive covenants were used not only for housing, but also to maintain segregated recreational spaces. In addition, the economic changes that came as a result of White flight, suburbanization, and inner city job loss brought with it a reduction in local government resources, including funds for public parks. These changes to the urban landscape disproportionately impacted low-income immigrant communities, including Latino neighborhoods. Health disparities researchers are concerned with the inequitable distribution of parks and recreation facilities because it may contribute to disparities in physical inactivity and obesity, health risks that disproportionately impact Latinos. However, much of the literature investigating disparities in the built environment fails to include a racial analysis. The current study uses a Critical Race Theory framework to examine disparities in park availability in Los Angeles. We used a unique park dataset created in ArcGIS to carry out a county-wide assessment of the availability of park features at the neighborhood level. Data come from two sources, the Los Angeles County Location Management System, which includes information on specific park features (e.g., swimming pools, parks and gardens, recreation centers) and the American Community Survey, which includes neighborhood-level sociodemographic information. A zero-inflated negative binomial regression model was used to test whether Latino immigrant neighborhood characteristics are associated with the availability of park features in Los Angeles. Results indicate that Latino immigrant neighborhoods have limited park availability. The discussion situates these findings of inequitable distribution of park resources in the appropriate social and historical context of Latinos living in Los Angeles.